Association between Glycemic Control and Clinic Attendance in Emerging Adults with Type 1 Diabetes: A Tertiary Center Experience. (9th July 2018) - Fisher, Eldad; Lazar, Liora; Shalitin, Shlomit; Yackobovitch-Gavan, Michal; de Vries, Liat; Oron, Tal; Tenenbaum, Ariel; Phillip, Moshe; Lebenthal, Yael
Abstract : Aims. The transition of emerging adults with type 1 diabetes (T1D) from pediatric diabetes clinics to adult clinics between 18 and 21 years of age could result in decreased clinic attendance and thus worsen glycemic control. Our institutional policy offering surveillance till age 30 enabled us to evaluate clinic attendance without the confounding effect of transition. Our aim was to determine the association between glycemic control (HbA1c) and attendance rate. Methods. The medical records of 261 (54% males) young adult T1D patients (median age 22.9 years) were reviewed. Patients were stratified according to the attainment/nonattainment of glycemic targets (HbA1c ≤ 7% versus HbA1c > 7% (53 mmol/mol)). The attendance rate was calculated as the number of clinic visits/number of scheduled appointments. Results. Median annual number of scheduled visits was 3 (3, 4); attendance rate was 75% (53.6%, 100%). Seventy-four (28.4%) patients attained glycemic targets (median HbA1c 6.5% (48 mmol/mol) (6.3%, 6.8% (45.51 mmol/mol)); 187 (71.6%) patients had a median HbA1c of 7.8% (62 mmol/mol) (7.4%, 8.4% (57.68 mmol/mol)). The attainment of the treatment target was more prevalent in older patients (P = 0.006 ), in male patients (P = 0.007 ), and in patients with higher education (P = 0.017 ). Higher attendance rate ( β (2.483), P < 0.001 ) and male gender ( β (0.746), P = 0.015 ) were associated with better metabolic control. Conclusions. In emerging adults with T1D during the ongoing stable phase of diabetes management, higher attendance rate, rather than absolute number of clinic visits, was associated with the attainment of glycemic targets.